2018
DOI: 10.3892/etm.2018.6794
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of epithelial cell adhesion molecule as a predictor of poor outcome in patients with hepatocellular carcinoma

Abstract: Cancer growth, metastasis and development are regulated by a number of genes, whose expression mediates important processes, including cellular plasticity, motility and internal interactions in the tumor microenvironment. The epithelial cell adhesion molecule (EpCAM) serves an important role in cell-cell migration and tumorigenicity, particularly metastasis. The aim of the present study was to measure EpCAM expression using immunohistochemistry and to investigate the association between clinicopathological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Kaplan–Meier analyses showed that at advanced clinical stages, high EpCAM expression and poor differentiation grade were associated with poor survival rates. These results collectively support the utility of EpCAM in HCC as a predictive biomarker for unfavorable prognosis [ 73 ].…”
Section: Identification and Plasticity Of Lcscssupporting
confidence: 75%
“…Kaplan–Meier analyses showed that at advanced clinical stages, high EpCAM expression and poor differentiation grade were associated with poor survival rates. These results collectively support the utility of EpCAM in HCC as a predictive biomarker for unfavorable prognosis [ 73 ].…”
Section: Identification and Plasticity Of Lcscssupporting
confidence: 75%
“…In HCC, the loss of HNF4 [9,51,56] and expression of the cancer stem cell (CSC) markers CD44, CK19, Sox9, and EpCAM are considered to be indicators for poor prognosis [57,58,59,60]. In N-HCC25, these CSC markers were expressed in all passages.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that EpCAM could be a potential target for the diagnosis and therapy of hepatic cancers. Yamashita et al demonstrated that activation of the Wnt/β-catenin signaling pathway stimulates EpCAM expression which, in turn, negatively affects the prognosis of HCC patients [ 103 , 104 ]. Wang et al [ 105 ] and Arzumanyan et al [ 106 ] demonstrated that hepatitis B antigen HBx promotes the self-renewal and tumorigenicity of EpCAM + hepatic progenitor cells by stimulating β-catenin signaling and miR-181 expression.…”
Section: Surface Marker-based Therapiesmentioning
confidence: 99%